2002
DOI: 10.1016/s0012-365x(01)00436-8
|View full text |Cite
|
Sign up to set email alerts
|

On generalized van der Waerden triples

Abstract: Van der Waerden's classical theorem on arithmetic progressions states that for any positive integers k and r, there exists a least positive integer, w(k, r), such that any r-coloring of {1, 2, . . . , w(k, r)} must contain a monochromatic kterm arithmetic progression {x, x + d, x + 2d, . . . , x + (k − 1)d}. We investigate the following generalization of w(3, r). For fixed positive integers a and b with a ≤ b, define N (a, b; r) to be the least positive integer, if it exists, such that any r-coloring of {1, 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…In Section 3 we show this conjecture to be false. We also obtain upper bounds on dor(a, b) for all (a, b) = (1, 1), which improve upon the results of [3], and provide an alternate proof that (1,1) is the only regular triple.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…In Section 3 we show this conjecture to be false. We also obtain upper bounds on dor(a, b) for all (a, b) = (1, 1), which improve upon the results of [3], and provide an alternate proof that (1,1) is the only regular triple.…”
Section: Introductionsupporting
confidence: 71%
“…It also uses the following lemma. In [3] it was shown that dor(1, 3) ≤ 3, dor(2, 3) = 2, and dor(2, 2) ≤ 5. By Lemma 1, these three facts cover Cases (i), (ii), and (iii), respectively.…”
Section: The Only Regular Triples Are Arithmetic Progressionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several other problems related to Schur numbers and Rado numbers have been considered [1][2][3]6,7,13,17,19]. In 2001, Robertson and Schaal introduced the concept of off-diagonal Rado numbers (or off-diagonal generalized Schur numbers) [18].…”
Section: Introductionmentioning
confidence: 99%